The role of vocational education in developing entrepreneurial competences of students - Perić, Julia (Array, 2020)
Entrepreneurship is defined as one of key lifelong competences and it represents ability to turn ideas into real projects. As such, it includes creativity, initiative, taking responsibility, taking risks, planning and managing projects. The development of entrepreneurial competences via formal education has become a priority for governments of a large number of European countries. Many EU documents emphasize the importance of investing into education that focuses on the development of entrepreneurial competences, as it directly affects students’ employment. However, this guideline represents a new challenge for the educational system – the need to change educational programs and organize them so that they influence the development of entrepreneurial competences, which enables students to become more employable and to cope with uncertainty, complexity and dynamics of the labor market. High unemployment rate of young people and challenges and demands of the labor market have led to a debate about the effectiveness and efficiency of educational programs at all levels. In this context, effectiveness and quality of vocational education and training (VET) are particularly important, since most vocational school students, after finishing secondary level, will not continue towards tertiary education, but will rather find themselves on the labor market. Therefore, vocational education should focus on the development of such skills (generic competences and vocational qualifications) that will correspond to the needs of the labor market, thus enabling easier and faster employment. The main purpose of this paper is to determine the extent to which vocational education contributes to development of students’ entrepreneurial competences. The data used in this paper comes from a survey that covered 1272 students from 15 secondary vocational schools in Osijek-Baranja County, one of the most underdeveloped regions in Croatia.